Composition of international capital flows: A survey - Koralai Kirabaeva; Assaf Razin (Bank of Canada, 2010)
We survey several key mechanisms that explain the composition of international capital flows: foreign direct investment, foreign portfolio investment and debt flows (bank loans and bonds). In particular, we focus on the following market frictions: asymmetric information in capital markets and exposure to liquidity shocks. We show that the information asymmetry between foreign and domestic investors leads to inefficient investment allocation and borrowing in a country that finances its domestic investment through foreign debt or foreign equity. Exposure to liquidity shocks due to the mismatch of debt maturity may induce banking crises and cause sudden reversals of short-term capital flows. When there is asymmetric information between sellers and buyers in the capital market, then due to the adverse selection foreign direct investment is associated with higher liquidation costs than portfolio investment. The difference in exposure to liquidity shocks (in addition to asymmetric information) can explain the composition of equity flows between developed and emerging countries, and the patterns of foreign direct investments during financial crises.
Keywords: F21; F34; D82; 330; International topics; Kapitalmobilität; Direktinvestition; Portfolio-Investition; Auslandsverschuldung; Asymmetrische Information; Adverse Selection; Moral Hazard; Theorie